2020
DOI: 10.1097/jtn.0000000000000503
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial on the Use of Antiseptic Solutions for the Pin-Site Care of External Fixators: Chlorhexidine–Alcohol Versus Povidone–Iodine

Abstract: Pin-site infections remain a common clinical complication in patients with external fixators. Pin-site care is commonly performed with either chlorhexidine–alcohol solution or povidone–iodine solution. This study aimed to investigate the superiority of chlorhexidine–alcohol solution versus povidone–iodine solution for external fixator pin-site care in pin-site infection. This prospective randomized clinical trial using an open, parallel-group design was conducted in a single Spanish hospital. Eligible consenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…14 Even if placement of skeletal traction through metallic pins becomes necessary, proper antiseptic measures should be taken to prevent pin-tracks infection and delayed osteomyelitis. 15 Courvoisier et al 11 and Hamahashi et al 12 have reported cases of delayed osteomyelitis in pin tracks previously (Table 1). There are not many cases in literature, especially with such a delayed presentation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…14 Even if placement of skeletal traction through metallic pins becomes necessary, proper antiseptic measures should be taken to prevent pin-tracks infection and delayed osteomyelitis. 15 Courvoisier et al 11 and Hamahashi et al 12 have reported cases of delayed osteomyelitis in pin tracks previously (Table 1). There are not many cases in literature, especially with such a delayed presentation.…”
Section: Discussionmentioning
confidence: 97%
“…Skin traction must be favored in cases where traction is needed for lower-extremity trauma 14. Even if placement of skeletal traction through metallic pins becomes necessary, proper antiseptic measures should be taken to prevent pin-tracks infection and delayed osteomyelitis 15…”
Section: Discussionmentioning
confidence: 99%
“…Jalon 19 randomised 128 patients and 568 pins to compare iodine and chlorhexidine for pin-site care in patients undergoing external fixation for clean or contaminated surgeries. Ultimately, they reported a 62% per-patient PSI in the chlorhexidine group vs a 68% PSI in the iodine group declaring no statistical difference.…”
Section: R Esultsmentioning
confidence: 99%